2020
DOI: 10.1055/s-0040-1721502
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Platelet Function Analyzer in Patients with Suspected Platelet Function Disorders: Diagnostic Accuracy Study

Abstract: Introduction The platelet function analyzer (PFA) is widely used as a screening tool for bleeding disorders in various settings. The diagnostic performance regarding platelet function disorders (PFDs), which are among the most common inherited bleeding disorders, is however still elusive. We aimed to assess the diagnostic value of PFA for PFD in clinical practice. Methods Comprehensive clinical and laboratory data of all consecutive patients referred to a specialized outpatient between January 2012 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
(78 reference statements)
0
11
1
Order By: Relevance
“…43 PFA-100 is not recommended as a screening test for PFD patients, 46 due to its low prevalence of prolonged closure times in comparison to healthy controls. 49,[61][62][63][64][65] In line, in the VIBB, 25% of all PFD patients did not show prolonged closure times with either PFA-100 with epinephrine or with ADP. 66 In our center, we perform LTA, flow cytometric mepacrine fluorescence, and glycoprotein expression analysis (►Fig.…”
Section: Platelet Function Defectsmentioning
confidence: 69%
“…43 PFA-100 is not recommended as a screening test for PFD patients, 46 due to its low prevalence of prolonged closure times in comparison to healthy controls. 49,[61][62][63][64][65] In line, in the VIBB, 25% of all PFD patients did not show prolonged closure times with either PFA-100 with epinephrine or with ADP. 66 In our center, we perform LTA, flow cytometric mepacrine fluorescence, and glycoprotein expression analysis (►Fig.…”
Section: Platelet Function Defectsmentioning
confidence: 69%
“…A study showed that platelets of neonates of preeclamptic mothers had a markedly higher responsiveness to agonists in vitro by flow cytometry; however, resting platelets of FGR neonates seemed to be in a slightly lower state of activation (47). Although the use of PFA as a screening tool for inherited platelet function disorders among adults has been questioned (48), prolongation of COL/EPI CT in the present study supports the impaired platelet function of FGR neonates reported from previous studies (13, 14, 47). It is of great importance that platelet hyporesponsiveness seems to apply for the whole group of FGR neonates irrespective of the cause.…”
Section: Discussionmentioning
confidence: 99%
“…9,12 Recent studies reported low sensitivity of the PFA in several mild platelet disorders. [11][12][13][14][15][16] Studies in pediatric populations show a similar heterogeneity. [17][18][19][20] The value of the studies investigating PFA to diagnose platelet function disorders in pediatric patients is limited, because most studies do not differentiate between specific IPFD diagnoses.…”
Section: Introductionmentioning
confidence: 85%
“…37,38 Similarly, in the other IPFD subgroup, we also measured median CTs that were not significantly longer than CTs of 'No diagnosis' patients. Kaufmann et al 16 included cases of α-SPD and reported only marginally prolonged CTs in all platelet function disorders. Our findings agree with most recent studies 16,20,37,38 reporting low sensitivity of the PFA to mild platelet function disorders.…”
Section: Diagnostic Performance Of the Pfa And The Isth-batmentioning
confidence: 99%